Assessing the role of peripheral CD8 T cells in neurocognitive impairment in HIV-infected men who have sex with men: data from the MSM Neurocog Study. (February 2015) - Rawson, TM; Dubb, S; Pozniak, A; Kelleher, WP; Mandalia, S; Gazzard, B; Barber, TJ
Studies have suggested CD8 lymphocytes may be a possible marker for inflammation, which is believed to be a contributing factor to neurocognitive impairment. Individuals enrolled in the MSM Neurocog Study were analysed. Those with depression, anxiety or mood disorders were excluded. Individuals with neurocognitive impairment were identified using the Brief NeuroCognitive Screen and compared to those with normal scores. CD4 and CD8 T cell values and CD4:CD8 ratios were compared between groups. In all, 144 men, aged 18–50 years, were included in the analysis. Twenty were diagnosed with neurocognitive impairment. We were unable to identify any significant difference between current, nadir or peak CD4 and CD8 counts. CD4:CD8 ratios and CD4:CD8 ratio inversion (<1) were also found to be similar between both groups. However, neurocognitive impairment subjects were 8% more likely to have inversion of CD4:CD8 ratio and higher median peak CD8 cell counts reported compared to non-impaired subjects. Analysis of data from the MSM Neurocog Study, demonstrated trends in peripheral CD8 counts and CD4:CD8 ratios. However, we are unable to demonstrate any significant benefit. Plasma biomarkers of neurocognitive impairment in HIV-infected subjects would be of great benefit over current methods of invasive CSF analysis and technical neuroimaging used in the diagnosis of neurocognitive impairment. Future, prospective, longitudinal work with large numbers of neurocognitive impairment subjects is required to further investigate the role of peripheral CD8 T cells as markers of neurocognitive impairment.